PENGUKURAN USABILITY APLIKASI WEB MENGGUNAKAN SUS (SYSTEM USABILITY SCALE) DAN PENGUJIAN BLACK BOX PADA WEBSITE E-LEARNING (GEN-IT) KABUPATEN KATINGAN - Saputra, Septian Dwi; Parhusip, Jadiaman (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The Gen-IT e-learning application plays a vital role in supporting the digitalization of education in Katingan Regency, making it essential to evaluate both its technical quality and user experience. This study aims to assess the feasibility of the Gen-IT application using two approaches: black box testing and usability evaluation. The black box testing method was applied to validate the core features from a technical perspective, while the System Usability Scale (SUS) method was used to evaluate user experience, involving 17 respondents. The black box test results showed that 100% of the test scenarios were successfully executed without errors. Meanwhile, the usability evaluation achieved an average SUS score of 90.74, categorized as “Excellent” with a grade of “A”. These combined findings indicate that the Gen-IT application not only demonstrates strong technical reliability but also provides an outstanding user experience, making it an effective digital learning tool.